EDUCATION IN GREEN CHEMISTRY : INCORPORATING GREEN CHEMISTRY IN SCHOOL CURRICULUM - Ravichandran, R. (SCHOOL SCIENCE, 2011)
In the midst of a more vigorous concern for the environment, several terms have been put forward to capture an important idea. They represent the supposition that chemical processes that carry environmental negatives can be replaced with less polluting or non-polluting alternatives. Chemistry has historically been part of the problem, but now we hope it can be part of the solution. Here, the term “Green Chemistry” will be the focus since it is now the most widely used term. The Green Chemistry is a perfect fit for a school curriculum committed to the well-being of its responsiblecitizens with core human values. The principles of Green Chemistry that can energise our classrooms and bring long-term meaning and direction to a component of academic research await clear definition.